Unaltered 3’-sialyllactose and 6’-sialyllactose concentrations in human milk acutely after endurance exercise: a randomized crossover trial - Lemoine, Maëliss Cynthia Chloé; Klau, Leesa J.; Holmen, Mads; Ashby, Emily Rose; Aachmann, Finn L.; Andreassen, Trygve; Giskeødegård, Guro F.; Moholdt, Trine (Frontiers in Nutrition, 2025)
IntroductionHuman milk contains over 200 different types of human milk oligosaccharides (HMOs) with concentrations varying based on genetics, lifestyle, and time postpartum. Prior research indicates that exercise training during pregnancy leads to increased milk concentration of the HMO 3′-sialyllactose (3’SL), potentially improving the offspring’s metabolic development. The acute effect of postpartum exercise on HMOs concentrations in human milk is unknown. We aimed to evaluate the acute effect of moderate- and high-intensity endurance exercise on two selected sialylated HMOs in human milk.MethodsTwenty exclusively breastfeeding mothers to 6-12-weeks-old term infants were included in this randomized crossover trial. They completed three conditions in random order: no exercise (REST), moderate-intensity continuous training (MICT), and high-intensity interval training (HIIT). We collected human milk at 07:00 h, 11:00 h (immediately after rest/exercise), 12:00 h (1 h after rest/exercise) and 15:00 h (4 h after rest/exercise). Skimmed milk was analyzed by NMR spectroscopy to determine concentrations of 3’SL and 6′-sialyllactose (6’SL). We used a linear mixed model to estimate the effect of exercise on the concentrations of the selected HMOs, compared with REST.ResultsAll participants completed the three conditions and were included in the analyses. Exercise had no statistically significant effect on 3’SL or 6’SL concentrations. The largest mean differences in 3’SL concentrations were observed immediately after rest/exercise: MICT yielded an increase of 10% (95% confidence interval (CI) -5 to 24%, p = 0.19) and HIIT of 4% (95% CI -10 to 19%, p = 0.55). Similarly, we observed the largest mean differences in 6’SL concentration immediately after MICT, with an increase of 5% (95% CI -6 to 15%, p = 0.40), whereas the greatest mean difference in 6’SL concentration was seen 1 h after HIIT (6%, 95% CI -5 to 16%, p = 0.31). No serious adverse events occurred.ConclusionA single endurance exercise session had no statistically significant effect on 3’SL or 6’SL concentrations in human milk. Further research should determine the effect of regular exercise training on HMO concentrations.Clinical trial registrationClinicalTrials.gov, NCT05042414.